Dexamethasone PLGA Microspheres for Sub-Tenon Administration: Influence of Sterilization and Tolerance Studies - Deyanira Barbosa-Alfaro; Vanessa Andrés-Guerrero; Ivan Fernandez-Bueno; María Teresa García-Gutiérrez; Esther Gil-Alegre; Irene Teresa Molina-Martínez; José Carlos Pastor-Jimeno; Rocío Herrero-Vanrell; Irene Bravo-Osuna (MDPI AG, 2021)
Many diseases affecting the posterior segment of the eye require repeated intravitreal injections with corticosteroids in chronic treatments. The periocular administration is a less invasive route attracting considerable attention for long-term therapies. In the present work, dexamethasone-loaded poly(lactic-co-glycolic) acid (PLGA) microspheres (Dx-MS) were prepared using the oil-in-water (O/W) emulsion solvent evaporation technique. MS were characterized in terms of mean particle size and particle size distribution, external morphology, polymer integrity, drug content, and in vitro release profiles. MS were sterilized by gamma irradiation (25 kGy), and dexamethasone release profiles from sterilized and non-sterilized microspheres were compared by means of the similarity factor (f2). The mechanism of drug release before and after irradiation exposure of Dx-MS was identified using appropriate mathematical models. Dexamethasone release was sustained in vitro for 9 weeks. The evaluation of the in vivo tolerance was carried out in rabbit eyes, which received a sub-Tenon injection of 5 mg of sterilized Dx-MS (20-53 µm size containing 165.6 ± 3.6 µg Dx/mg MS) equivalent to 828 µg of Dx. No detectable increase in intraocular pressure was reported, and clinical and histological analysis of the ocular tissues showed no adverse events up to 6 weeks after the administration. According to the data presented in this work, the sub-Tenon administration of Dx-MS could be a promising alternative to successive intravitreal injections for the treatment of chronic diseases of the back of the eye.